Electronic-Supplement Kimiapedia dengan Pendekatan Literasi Sains pada Materi Hidrokarbon di SMA Negeri 10 Pontianak - Eka Sofia; Rini Muharini; Ira Lestari; Rachmat Sahputra; Maria Ulfah (Universitas Pendidikan Mandalika Mataram, 2022)
This study aims to determine the level of feasibility and response of students and educators to the e-supplement Kimiapedia with a scientific literacy approach on hydrocarbon material at SMA Negeri 10 Pontianak. This research uses research and development methods, and the research model is adopted from analysis, design, development, implementation, and evaluation, the stages carried out to the development stage. The feasibility level of the e-supplement chemistrypedia approach to scientific literacy on hydrocarbon material gets a value of 96% with a very feasible category which is the accumulation of the average validation of linguists, media and teaching materials experts and material experts. The limited-scale response test result gave students’ response value of 74% in which was categorized as a good category. Further bigger scale response test showed similar 75% in good category. In addition, teacher response test showed very good-category in both value with 94,7% and 95.7%. This result implied that the material was acceptable and can be applied in chemistry learning.